Flavonoid accumulation during florescence in three Chrysanthemum morifolium Ramat cv.'Hangju'genotypes - Wang, T.; Guo, Q.; Mao, P.
This paper focuses on the development of a rapid and reliable HPLC method for the simultaneous determination of the flavonoids quercetin, luteolin, apigenin and acacetin in Chrysanthemum morifolium cv. Hangju capitulum in China. The comparison of the trend in flavonoid accumulation during florescence in 3 C. morifolium cv. Hangju genotypes at different flowering stages are also presented.
Keywords: ANALYTICAL METHODS; CHEMICAL COMPOSITION; CHRYSANTHEMUMS, DETECTION, FLAVONOIDS, FLOWERING; FLOWERS; GENOTYPES; HPLC; PLANT COMPOSITION